2004
DOI: 10.1021/ja044827v
|View full text |Cite
|
Sign up to set email alerts
|

Metal and Ligand K-Edge XAS of Organotitanium Complexes:  Metal 4p and 3d Contributions to Pre-edge Intensity and Their Contributions to Bonding

Abstract: Titanium cyclopentadienyl (Cp) complexes play important roles as homogeneous polymerization catalysts and have recently received attention as potential anticancer agents. To systematically probe the contribution of the Cp to bonding in organotitanium complexes, Ti K-edge XAS has been applied to TiCl(4) and then to the mono- and bis-Cp complexes, TiCpCl(3) and TiCp(2)Cl(2). Ti K-edge XAS is used as a direct probe of metal 3d-4p mixing and provides insight into the contribution of the Cp to bonding. These data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
136
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(161 citation statements)
references
References 44 publications
25
136
0
Order By: Relevance
“…Hence, in the solution-phase DFT calculations the 4 t 2 * orbitals are reasonably described as resulting from primarily metal n d and S 3p mixing. Because the solution-phase molecular orbital picture agreed better with previous theoretical models used to evaluate MS 4 2- , MO 4 2- , and MCl 4 ligand K-edge XAS spectra, 58,59,73-77 and in light of the gas- vs. solution-phase TDDFT results ( vide infra ), the solution-phase DFT data appeared to provide a more relevant model than the gas-phase calculations. Consistently, others have observed that including solvent dielectrics improves DFT agreement with XAS experimental data for anionic species.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…Hence, in the solution-phase DFT calculations the 4 t 2 * orbitals are reasonably described as resulting from primarily metal n d and S 3p mixing. Because the solution-phase molecular orbital picture agreed better with previous theoretical models used to evaluate MS 4 2- , MO 4 2- , and MCl 4 ligand K-edge XAS spectra, 58,59,73-77 and in light of the gas- vs. solution-phase TDDFT results ( vide infra ), the solution-phase DFT data appeared to provide a more relevant model than the gas-phase calculations. Consistently, others have observed that including solvent dielectrics improves DFT agreement with XAS experimental data for anionic species.…”
Section: Resultssupporting
confidence: 51%
“…41,47,59,70,71,77,81-88 The computed spectra were carried out using linear response theory, based on density functional theory. This formalism is commonly referred in the community as TDDFT as it is from the time-dependent perturbation theory to DFT.…”
Section: Resultsmentioning
confidence: 99%
“…36 ,4o,s4 The TD DFT simulated CI K-edge XAS for (CsMe5)2MCI2 (Ti, 1; Zr, 2; andHf, 3) agree well with the experimental data and show two pre-edge features for 1 and 2, and tlu'ee features for 3, Figure 6. 3 is attributed to a CI Is -;.…”
Section: Hybrid-dft Spectral Simulations Time Dependent Density Funcsupporting
confidence: 61%
“…These differences in pre-edge areas can be understood as a direct reflection of the lower centrosymmetry of the individual iron centers in 1 due to the increased covalency of the oxo ligand that serves to further mediate iron 3d-4p mixing. 5051 …”
Section: Results and Analysismentioning
confidence: 99%